2014
DOI: 10.1097/aln.0000000000000462
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and Increased Hypercarbic Drive Impair the Coordination between Breathing and Swallowing

Abstract: Background Coordination between breathing and swallowing helps prevent aspiration of foreign material into the respiratory tract. We examined the effects of anesthesia, and hypercapnia on swallowing-breathing coordination. Methods In a randomized controlled cross-over study, general anesthesia with propofol or sevoflurane was titrated using an up-down method to identify the threshold for suppression of the motor response to electrical stimulation of the forearm. Additional measurements included bispectral in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Hypoxia has also been studied in nonnutritive swallow in newborn lambs which showed a decrease in frequency during quiet sleep (Duvareille et al, 2007). Interestingly, hypercapnia shifts swallows towards In and Ex-In (D’Angelo et al, 2014) while we found that hypocapnia with hypoxia shifts swallow toward In-Ex. In light of the present data, further studies may need to investigate swallow-breathing coordination not only with variation of respiratory drive but swallow drive as well.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Hypoxia has also been studied in nonnutritive swallow in newborn lambs which showed a decrease in frequency during quiet sleep (Duvareille et al, 2007). Interestingly, hypercapnia shifts swallows towards In and Ex-In (D’Angelo et al, 2014) while we found that hypocapnia with hypoxia shifts swallow toward In-Ex. In light of the present data, further studies may need to investigate swallow-breathing coordination not only with variation of respiratory drive but swallow drive as well.…”
Section: Discussionmentioning
confidence: 62%
“…Specifically, alterations in respiratory mechanics due to chronic obstructive pulmonary disease (Nagami et al, 2017; Pinto et al, 2017) and/or upper abdominal laparotomy can shift swallow occurrences to inspiration, potentially increasing risk of aspiration (Pitts et al, 2015b). Additionally, there is also limited evidence that alterations in blood gasses (i.e., oxygen [O 2 ] and carbon dioxide [CO 2 ]) can also increase the likelihood that swallow will occur during inspiration (D’Angelo et al, 2014), (Ghannouchi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of swallowing ability, EMG 11,12 , manometry 13,14 , timing of swallowing 14 , radiography 13 , or fibreoptic endoscopic evaluation of swallowing 15 was used. Radiography or manometry may be superior to electromyography; however, the insertion of a catheter can influence salivary secretion 16 .…”
Section: Discussionmentioning
confidence: 99%
“…during hypercapnic respiratory failure) can lead to high transpulmonary pressure during inspiration, which increases lung stress. Supplementation of inhaled carbon dioxide was shown to reverse upper airway collapsibility induced by propofol 13 , but excessive hypercapnia increases the likelihood of pathological swallowing 14 . Thus, perioperative physicians need to balance their interventions to keep ventilatory drive within normal limits.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Sedation commonly leads to upper airway dysfunction, resulting in insufficient respiration (hypopnea/apnea) but also affects the breathing–swallowing coordination and pharyngeal muscle strength, both of which contribute to pharyngeal dysfunction and increased risk of aspiration 12 . Supplementation of inhaled carbon dioxide was shown to reverse upper airway collapsibility induced by propofol 13 , but excessive hypercapnia increases the likelihood of pathological swallowing 14 . Thus, perioperative physicians need to balance their interventions to keep ventilator drive within normal limits.…”
Section: Pathophysiologymentioning
confidence: 99%